Making a new beginning based on drawing… educational paths in nursery and primary school - Franca Zuccoli (Disegnare con, 2019)
How may we relate child drawing to that produced by adults? Under what conditions may children’s graphic productions be viewed as key steps towards constructing knowledge and intensifying their gaze? This paper proposes possible lines of interpretation and action, which, in keeping with numerous existing studies, take drawing to be a crucial dimension within a broader developmental trajectory. Children’s drawing has been a focus of interest in the field of didactics and pedagogy - and studied in increasing depth - since 1887, when historian and archaeologist Corrado Ricci published a book on the topic entitled L’arte dei bambini [Children’s Art]. The many studies, especially in the fields of psychology and education, that have been conducted to date have variously interpreted children’s drawing as a visible and verifiable sign of the development of intelligence or, in contrast, as fulfilling purely communicative and emotional purposes, that is to say, as a manifestation of feeling. Differing interpretations of children’s graphic art have also been proposed based on how their productions are viewed. Some authors attribute children with artistic capacities, in the broadest sense of the term, while others define both their early scribbles and later, more defined drawing work as a medium for experimentation as they progressively encounter objective reality. In this paper, after offering a brief overview of some of the more representative studies and turning points in the history of children’s art, I focus on the potential inherent in childhood drawing, with a view to defining some of its aims and functions, including the potential ways in which it can engage with artistic heritage. DOI: https://doi.org/10.20365/disegnarecon.23.2019.1